2000
DOI: 10.2166/wst.2000.0150
|View full text |Cite
|
Sign up to set email alerts
|

Options for beneficial reuse of biosolids in Victoria

Abstract: This paper presents a synopsis of current biosolids management in Victoria as well as an overview of some biosolids processing technologies. Indicative capital and annual costs to upgrade wastewater sludge management facilities at Victorian wastewater treatment plants to maximise safe beneficial reuse of biosolids and sludge products are provided. The data will be particularly useful for preliminary assessment and planning purposes of biosolids management strategies for government, non-metropoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Ideal C/N ratio for sewage sludge composting should range from 26-31 (Oorschot et al, 2000). If C/N ratio is higher than this, organisms will not find enough nitrogen, have their growth limited, and the process will become slower, not reaching the temperature required for pathogen destruction.…”
Section: Control Parameters and Environmental Requirementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideal C/N ratio for sewage sludge composting should range from 26-31 (Oorschot et al, 2000). If C/N ratio is higher than this, organisms will not find enough nitrogen, have their growth limited, and the process will become slower, not reaching the temperature required for pathogen destruction.…”
Section: Control Parameters and Environmental Requirementsmentioning
confidence: 99%
“…Several studies (Oorschot et al, 2000;EPA, 1992EPA, , 1994 have shown that the addition of 30-50% of CaO on a dry weight basis (0.3 to 0.5 kg CaO per kgTS) to sludge leads to biosolids with pathogenic organisms below the detection threshold. Hydrated lime can also be used, although a significant increase in sludge temperature is not attained, therefore requiring a longer contact time.…”
Section: Dewatered Sludgesmentioning
confidence: 99%